Endoscopic Interlaminar Management of Lumbar Disc Disease - Yadav, Yad Ram; Parihar, Vijay; Namdev, Hemant; Agarwal, Moneet; Bhatele, Pushp Raj (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Introduction The role of surgery by minimally invasive techniques for lumbar disc disease remains unclear in the Cochrane review. There are reports of significant advantages of endoscopy over open or microdiscectomy techniques, such as better visualization of the lesion, smaller incision sizes with lower short-term morbidity, reduced hospital stay, and better education.Materials and Methods Four hundred consecutive lumber disc herniation patients underwent endoscopic interlaminar lumbar discectomy from January 2006 to December 2010 by single surgeon by Destandu system (Karl Storz, Germany). Single-level and double-level disc with unilateral or bilateral symptoms (including central, sequestrated, or migrated disc) were included. Visual analog scale (VAS) scores for back pain and leg pain and MacNab criteria were recorded pre- and postoperatively.Results The mean VAS score before surgery was 7.9 as compared with a 1.5 score 3 months after surgery. Postoperative VAS scores were significantly better in 90% of cases. Overall, 91% of patients had good-to-excellent results according to MacNab criteria. Accidental intraoperative single-facet injury, minor dural tear, recurrence, postoperative discitis, and persistent paresthesia were seen in 3, 7, 2, 2, and 1 patients, respectively. The mean follow- up was 24 months (range 10 months to 5 years).Conclusions Endoscopic interlaminar technique (ILT) was a safe and effective alternative procedure for lumber disc disease. This was associated with some complications, especially in the initial learning curve. Once the practitioner is over the learning curve and has acquired expertise, this procedure was safe and effective.
Keywords: lumbar disc herniation; spinal endoscopy; percutaneous lumbar disc decompression; endoscopic lumbar discectomy